PENGARUH RETURN ON EQUITY DAN DEBT TO EARNING RATIO TERHADAP HARGA SAHAM DENGAN EARNING PER SHARE SEBAGAI VARIABEL INTERVENING (Studi Kasus Perusahaan Sektor Hotel, Restoran dan Pariwisata yang Terdaftar di BEI 2016-2019) - Teguh Erawati; Hilda Noer Alawiyah (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to examine the effect of return on equityand debt to equity ratio on stock prices with earnings per share as an intervening variable. The sample used is the hotel, restaurant, and tourism sub-sector companies during 2016-2019, based on the purposive sampling method obtained from 10 companies. The data testing method used is multiple linear regression analysis and path analysis which is processed using the IBM SPSS version 20 tool. The results showed that return on equity has a positive effect on earnings per share, while debt to equity per share does not affect earnings per share. The results of this study also conclude that earnings per share have a positive effect on stock prices. Return on equity and debt to equity ratio does not affect stock prices. Return on equity and debt to equity ratio through earnings per share affect stock prices